Microbial Cell Factories for Green Production of Vitamins - Wang, Yanyan; Liu, Linxia; Jin, Zhaoxia; Zhang, Dawei (Frontiers in Bioengineering and Biotechnology, 2021)
Vitamins are a group of essential molecules which is necessary to regulate metabolic activities and maintain optimal health. There are widely applications of vitamins in food, cosmetics, feed, medicine and other industries. The increased globally demand of vitamins contributes to the people's interest for vitamins production strategies. Chemical synthesis and microbial fermentation are two mainly production methods. Chemical synthesis methods are often used severe process conditions, toxic compound and non-renewable chemicals which are costly and easily caused safety problems, serious pollution and hazardous waste. Microbial cell factories for vitamins production are green and sustainable for both the environment and economics. In this review, we summarized the vitamins which can be potential produced or have been used for commercial fermentation process. They include water-soluble vitamins (vitamin B complex and vitamin C) and fat-soluble vitamins (vitamin E and vitamin K). Further, metabolic engineering and the bioprocess engineering are discussed to display construction of microbial cell factories. We also highlight the current state and problems encountered for fermentative production of vitamins.